Assessing Connections Between Behavior Change Theories Using Network Analysis. Issue 5 (22nd May 2015) - Gainforth, Heather L.; West, Robert; Michie, Susan
Abstract: Background: A cross-disciplinary scoping review identified 83 of behavior change theories, with many similarities and overlapping constructs. Investigating the derivation of these theories may provide further understanding of their contribution and intended application. Purpose: To develop and apply a method to describe the explicit derivation of theories of behavior change. Methods: A network analysis of the explicit "contributing to" relations between the 83 theories was conducted. Identification of relations involved textual analysis of primary theory sources. Findings: One hundred and twenty-two connections between the theories were identified amounting to 1.8 % of the number possible. On average, theories contributed to one or two theories (mean = 1.47 ± 3.69 contributions) and were informed by one or two theories (mean = 1.47 ± 1.61 contributing theories). Discussion: Most behavior change theories appear to be explicitly informed by few prior theories. If confirmed, this suggests a considerable dislocation between generations of theories which would be expected to undermine scientific progress.